2014
DOI: 10.3390/nu6051913
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Metabolite Profiles in Premature Infants Show Early Postnatal Metabolic Adaptation and Maturation

Abstract: Objectives: Early nutrition influences metabolic programming and long-term health. We explored the urinary metabolite profiles of 48 premature infants (birth weight < 1500 g) randomized to an enhanced or a standard diet during neonatal hospitalization. Methods: Metabolomics using nuclear magnetic resonance spectroscopy (NMR) was conducted on urine samples obtained during the first week of life and thereafter fortnightly. Results: The intervention group received significantly higher amounts of energy, protein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 48 publications
(82 reference statements)
3
41
1
1
Order By: Relevance
“…The glycine, in particular, reached higher contents in neonates with fetal malnutrition. A similar difference in the levels of glycine has been recently observed between neonates small for gestational age (SGA) and controls [15]. Taurine belongs to the sulfur-containing amino acids; it is basic for neonates playing a key role in cell membrane stabilization, modulation of intracellular calcium levels, osmoregulation, and detoxification [16].…”
Section: Discussionmentioning
confidence: 71%
“…The glycine, in particular, reached higher contents in neonates with fetal malnutrition. A similar difference in the levels of glycine has been recently observed between neonates small for gestational age (SGA) and controls [15]. Taurine belongs to the sulfur-containing amino acids; it is basic for neonates playing a key role in cell membrane stabilization, modulation of intracellular calcium levels, osmoregulation, and detoxification [16].…”
Section: Discussionmentioning
confidence: 71%
“…We also found that for infants without an AKI diagnosis, glycine was important to the correlation with gestational age. Both metabolites have been discussed previously in urinary metabolomics of neonates as markers of insufficient growth in utero [51, 52]. It has been suggested that because both of these amino acids are glucogenic; an increase of glycine would cause a reduction of amino acid oxidation or reduced glucogenesis as a means of conservation [53].…”
Section: Discussionmentioning
confidence: 99%
“…The cross validation revealed a Q 2 value of greater than 0.5 is usually considered to be a good classification model [ 20 ]. The ratio Q 2 /R 2 is a measure of cross-validation reproducibility and Q 2 /R 2 above 0.5 are considered indicative of relevant associations [ 21 ]. A permutation test can evaluate whether the specific classification of the individuals in the two designed groups is significantly better than any other random classification in two arbitrary groups [ 22 ].…”
Section: Methodsmentioning
confidence: 99%